Gambaran Kepatuhan Perawat Dalam Pendokumentasian Asuhan Keperawatan Di Ruang Rawat Inap Cemara Rumah Sakit Bina Kasih Pekanbaru - Widyaningsing, Tri; Suhaemi, Ihsan; Ovari, Isna (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2024)
Nurse compliance is the key to success in documenting nursing care. Incomplete documentation will result in losses for patients because important information related to their care and health conditions is overlooked. The aim of this research is to determine the description of nurses' compliance in documenting nursing care in the Cemara inpatient room at Bina Kasih Hospital, Pekanbaru.This research is an description This research was conducted in November 2023. The population in this study was all nurses at Binakasih Hospital Pekanbaru, namely 32 people. The sampling technique uses total sampling. The measuring tool in this research uses a questionnaire. Data analysis in this study used univariateThe research results showed that 25 people (78.1%) were compliant in documenting nursing care, 27 respondents were complete in documenting nursing care. It is hoped that hospitals will continuously improve supervision by team leaders and heads of rooms regarding the completeness of nursing care documentation.